2020
DOI: 10.21203/rs.3.rs-91196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to negative socio-emotional events induces sustained alteration of resting-state brain networks in the elderly

Abstract: While basic emotional functions seem preserved in the elderly, adaptive brain mechanisms required to cope with socio-emotional stressful events remain unresolved and scarcely investigated in this population. To evaluate how the aging brain reacts during and after emotionally challenging social events, we designed a new "task-rest" paradigm in which elderly participants (N=127) underwent functional magnetic resonance imaging (fMRI) while exposed to socio-emotional videos. We unveil neural markers of "emotional… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Weaker resting-state functional connectivity between the right amygdala and PCC has previously been linked to greater reappraisal success (i.e., effective down-regulation of negative emotion) in younger adults ( Uchida et al, 2015 ), whereas increased amygdala-PCC resting-state functional connectivity has been observed following exposure to an acute stressor ( Veer et al, 2011 ). More recently, Baez-Lugo et al (2021) reported that greater right amygdala-PCC functional connectivity following exposure to videos containing highly negative emotional content (i.e., people suffering) was significantly correlated with higher rumination, anxiety, and stress in elderly individuals ( Baez-Lugo et al, 2021 ). Critically, those older adults who self-reported more frequent negative thoughts after watching the negative emotional videos were those who also exhibited stronger right amygdala-PCC connec-tivity.…”
Section: Discussionmentioning
confidence: 99%
“…Weaker resting-state functional connectivity between the right amygdala and PCC has previously been linked to greater reappraisal success (i.e., effective down-regulation of negative emotion) in younger adults ( Uchida et al, 2015 ), whereas increased amygdala-PCC resting-state functional connectivity has been observed following exposure to an acute stressor ( Veer et al, 2011 ). More recently, Baez-Lugo et al (2021) reported that greater right amygdala-PCC functional connectivity following exposure to videos containing highly negative emotional content (i.e., people suffering) was significantly correlated with higher rumination, anxiety, and stress in elderly individuals ( Baez-Lugo et al, 2021 ). Critically, those older adults who self-reported more frequent negative thoughts after watching the negative emotional videos were those who also exhibited stronger right amygdala-PCC connec-tivity.…”
Section: Discussionmentioning
confidence: 99%